Diurnal dynamics of streamflow in an upland forested micro‐watershed during short precipitation‐free periods is altered by tree sap flow. Issue 13 (29th January 2016) - Deutscher, Jan; Kupec, Petr; Dundek, Peter; Holík, Ladislav; Machala, Martin; Urban, Josef
Abstract: Diurnal variations in streamflow are becoming acknowledged as a way of analysing how changing climatic conditions and land use affects watersheds but also as a way to understand watersheds as a whole. Yet not many studies from uplands below 900 mm mean annual precipitation zone are available from European countries. During the 2012 growing season, a sampling campaign took place in an upland forested micro‐watershed, Czech Republic (65 ha). Tree sap flow, rainfall and temperature were measured continuously, while streamflow at the discharge point and soil moisture were estimated from short‐term measurements. Short precipitation‐free periods lasting several days were identified for evaluation of trends in diurnal dynamics of both sap flow and streamflow. The results demonstrated that during these periods, the main factor altering streamflow was almost exclusively tree sap flow. A decrease in streamflow was observed during the day and an increase at night. The decline in sap flow after sunset was accompanied by a continuous increase in streamflow throughout the night up to its initial maximum in the morning. The amplitude in diurnal variations reached 18%. The observed time lag between the diurnal variations of sap flow and streamflow was approximately 2 h. Relatively low changes in diurnal dynamics of streamflow pointed out a strong regulatory role of the forest in buffering water discharge from the catchment. Copyright © 2015 John Wiley & Sons, Ltd.